Behaviour of Saffron (Crocus sativus L.) Corms for Daughter Corm Production - Nagoo, F.A. Nehvi, M.A. Khan*, Sabeena Naseer, Shaheena (Journal of Phytology, 2011)
Behaviour of saffron corms for daughter corm production has a paramount importance for commercial scale corm production under efficient nursery management system. Saffron corms weighing 1g to 16 g were planted in nylon nets, replicated twice for daughter corm production under annual planting cycle. Five corms were planted under each category supplemented with adequate nutrients. Maximum daughter corm production was observed in corms weighing above 15g, followed by corms weighing from 14g-10g. No substantial increase in number and weight of corms have been observed for corms weighing between 1g to 4g. However, under 5-7g category there was substantial increase in number of corms associated with bigger size daughter corms. Average diameter of daughter corms ranged from 18.48mm (8g) to 8.80 mm (1g). Maximum number of daughter corms/mother corm (3.3) were observed in bigger corms weighing 15 g and least number of daughter corms (0.6) were observed in 2 g category. Study reveals that initial corm weight has paramount effect on daughter corm production.